An Interesting Case Of A Horseshoe Kidney With Unilateral Single Ureter And Associated Anorectal Malformation - Karamnabi Siddiqui, Mohammed Ayub; Potdar, Ojas Vijayanand; Sharma, Shashank; Shaw, Vivek; Vaidya, Kaustubh; Sarwade, Prashant; Rathi, Darshan (Journal of Society of Surgeons of Nepal, 2023)
Horseshoe kidney (HSK) has an incidence of about 1 in 400 or 0.25% of the general population and is seen more commonly in males as compared to women in a ratio of 2:1. Usually, Horseshoe kidney would have two normal ureters each draining separately into the bladder. We present a rare and interesting case of Horseshoe kidney with unilateral single ureter and associated anorectal malformation.